1982
DOI: 10.1002/bem.2250030206
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2.45‐GHz CW microwave radiation on spontaneously beating rat atria

Abstract: The chronotropic and inotropic effects of 2.45-GHz continuous wave (CW) microwave radiation were investigated in the isolated spontaneously beating rat atria. Isolated atria were placed in specially designed tubes inserted into a waveguide exposure system. The atria were then irradiated for a period of 30 min, followed by a 30-min recovery period. The control atria were prepared simultaneously and sham exposed. Experiments were conducted at two temperatures, 22 and 37 degrees C, and two specific absorption rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…No microwave-specific influence on the heartbeat rate of isoated rat hearts was found at SARs of 2 or 10 W/kg. This result may be compared with that of Galvin et al [1982], who found no effect of microwave exposure (2,450 MHz) at an SAR of 2 or 10 W/kg on the contractile force in an isoalted rat's atria, where the beat rate was similar to that which occurs in the intact animal.…”
Section: Discussionmentioning
confidence: 52%
“…No microwave-specific influence on the heartbeat rate of isoated rat hearts was found at SARs of 2 or 10 W/kg. This result may be compared with that of Galvin et al [1982], who found no effect of microwave exposure (2,450 MHz) at an SAR of 2 or 10 W/kg on the contractile force in an isoalted rat's atria, where the beat rate was similar to that which occurs in the intact animal.…”
Section: Discussionmentioning
confidence: 52%
“…The data on the in vitro effects of microwave irradiation on cardiac tissue are also equivocal. There are reports that exposure to microwaves can cause a bradycardia (Olson et al, 1977), as well as data showing there are no chronotropic effects (Galvin et al, 1982a;Kaplan et al, 1971).…”
Section: Introductionmentioning
confidence: 99%